2020
DOI: 10.3389/fmicb.2020.00078
|View full text |Cite
|
Sign up to set email alerts
|

HDAC6, A Novel Cargo for Autophagic Clearance of Stress Granules, Mediates the Repression of the Type I Interferon Response During Coxsackievirus A16 Infection

Abstract: Autophagic cargoes ensure selective autophagy for the recognition and removal of various cytosolic aggregated proteins, damaged organelles, or pathogens. Stress granules (SGs), as antiviral immune complexes, serve a positive role in the type I interferon (IFN) response and can be targeted by autophagy (termed granulophagy). However, the cargo of granulophagy remains elusive, and it is still unknown whether granulophagy plays a role in viral infection. Here, we found that histone deacetylase 6 (HDAC6), a compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…These include for example components of mTORC1 complex, JNK and its scaffold protein WDR62, the ubiquitin peptidase USP10, the protein arginine methyltransferase (PRMT) 1 and PRMT5, the glycosyltransferase OGG1, and the poly-ADP-ribose polymerase PARP12 [70,408]. Accordingly, proteins within SGs were found to carry a plethora of posttranslational modifications including phosphorylation [250,409], GlcNac glycosylation [408], sumoylation [410], neddylation [411], ubiquitination [380], and ADP-ribosylation [264].…”
Section: Sgs As Signaling Hubs To Coordinate the General Stress Responsementioning
confidence: 99%
See 1 more Smart Citation
“…These include for example components of mTORC1 complex, JNK and its scaffold protein WDR62, the ubiquitin peptidase USP10, the protein arginine methyltransferase (PRMT) 1 and PRMT5, the glycosyltransferase OGG1, and the poly-ADP-ribose polymerase PARP12 [70,408]. Accordingly, proteins within SGs were found to carry a plethora of posttranslational modifications including phosphorylation [250,409], GlcNac glycosylation [408], sumoylation [410], neddylation [411], ubiquitination [380], and ADP-ribosylation [264].…”
Section: Sgs As Signaling Hubs To Coordinate the General Stress Responsementioning
confidence: 99%
“…First indications for such a model came from reports on the role of autophagy in clearing poly(I:C)-induced SGs [ 267 ]. Recent work on coxsackievirus A16 revealed that SGs induced early during infection were later cleared by autophagy as a means to suppress antiviral immune signaling [ 380 ]. Some viruses hijack the autophagic degradation pathway or use autophagosome-derived compartments to support their replication [ 381 , 382 ].…”
Section: Antiviral Sg Functions Beyondmentioning
confidence: 99%
“…P62 is the first selective autophagy adaptor protein discovered in mammals (96,97), and plays multiple roles in autophagy, including participating in the formation of aggresomes (98,99), anchoring the aggresomes to the autophagosome (100), and the degradation of aggresomes in selective autophagy (101,102). Accumulating evidence indicates that the interaction between HDAC6 and p62 is curial for autophagy (23,39,86,91,(103)(104)(105)(106)(107)(108). As mentioned above, HDAC6 and p62 work as two ubiquitin-binding proteins required for efficient autophagy that target protein aggregates and damaged mitochondria (23,91).…”
Section: The Relationship Of Hdac6 and P62 In Autophagymentioning
confidence: 99%
“…Interestingly, in human monocytes (THP-1) infected with RNA viruses such as Sendai virus (SeV), vesicular stomatitis virus (VSV), or encephalomyocarditis virus (EMCV), CCDC50 expression is significantly enhanced, and CCDC50 specifically recognizes polyubiquitinated RLRs, resulting in the delivery of activated RIG-I/MDA5 into autophagosomes for degradation ( Figure 2 ) ( Hou et al., 2021 ). Histone deacetylase 6 (HDAC6), a component of viral RNA-induced stress granules, acts as an antiviral immune complex and plays an active role in the type I IFN responses ( Zheng et al., 2020 ). Coxsackievirus A16 (CA16) triggers p62-mediated selective autophagic degradation of HDAC6, inhibits type I IFN responses, and promotes viral replication ( Figure 2 ) ( Zheng et al., 2020 ).…”
Section: Autophagy Is Manipulated By Virusesmentioning
confidence: 99%